The knowledge, attitudes, and practices of nurses at general hospitals in Guangdong Province regarding suicide prevention for inpatients and its influencing factors - Jinling Zhu; Meizhu Ding; Dongxu Si; Yingna Li; Zenghong Yuan; Danni Li; LiLi Deng; Cuiying Tang; Shuyun Xiong (BMC Nursing)
Abstract Background Nurses play the role of “gatekeepers” in suicide prevention for hospitalized patients. This study aimed to explore the knowledge, attitudes, and practices (KAP) of general hospital nurses in Guangdong Province regarding suicide prevention in hospitalized patients and analyze the factors influencing these aspects. Methods A convenience sampling method was employed to survey general hospital nurses in Guangdong Province using the Questionnaire Star platform. Data were collected using a self-designed general information questionnaire, a KAP questionnaire on nurses’ suicide prevention for hospitalized patients, the Perceived Social Support Scale, and the Work Engagement Scale. A total of 418 responses were submitted, with 12 invalid questionnaires excluded, yielding 406 valid questionnaires (valid response rate: 98.5%). Univariate analysis, multiple linear regression, and continuous variable forest plots were used to analyze the influencing factors. Results A total of 406 nurses were included in the study, with an average age of 32.15 years (SD = 7.19), of which 93.8% were female. Nurses’ work experience ranged from 0 to 37 years, with an average of 10.18 years (SD = 7.35). Among the study participants, 62.8% were married, 74.6% had a bachelor’s degree or higher, 63.1% had never experienced a suicide incident among hospitalized patients, and 86.5% of their departments had a suicide prevention plan. The results of the multiple regression analysis showed that nurses’ suicide prevention knowledge scores were significantly influenced by the following factors: participation in suicide prevention training ( β = 3.42, P < 0.001), use of suicide risk assessment tools ( β = 2.19, P < 0.05), perceived social support ( β = 0.12, P = 0.00231), and work engagement ( β = 0.19, P < 0.001). Nurses in “other” work roles scored significantly lower on knowledge ( β= -4.38, P < 0.05). In terms of suicide prevention attitudes, perceived social support ( β = 0.12, P < 0.001) and work engagement ( β = 0.08, P < 0.001) significantly improved attitude scores. Regarding suicide prevention practices, participation in suicide prevention training ( β = 2.60, P < 0.001) and use of suicide risk assessment tools ( β = 3.20, P < 0.05) were the main factors influencing practice scores. Conclusion The KAP of nurses in Guangdong Province’s general hospitals regarding suicide prevention for hospitalized patients is at a moderate level. Systematic suicide prevention training, enhancing nurses’ perceived social support, and improving work engagement are key measures to improve their KAP related to suicide prevention. The study provides empirical evidence for hospital managers to implement effective suicide prevention training and strengthen nurses’social support, and policymakers can use these findings to develop targeted policies to enhance hospital suicide prevention capabilities. Clinical trial number Not applicable.